Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2025)
:Table of Content • The Impact of Blockchain Technology Adoption on Audit Planning: An Exploratory Study on Saudi Audit Firms (2022-2023) Mr. Abdulaziz Ali Alzahrani ,Dr. Yousef Ali Alwardat, Dr. Mohammad Aboalkar Wazzan • The Impact of Strategic Leadership on Enhancing Organizational Reputation: A Field Study on Administrative Employees at King Abdulaziz University in Jeddah Governorate Mr. Saleh Jamaan Saleh Al-Zahrani • Impact of Modern Digitization of Logistics Operations on Supply Chain Performance: A Case Study of Almarai Company, Saudi Arabia Asst-Prof. Hanan Rashid Albalwy • The role of governance in raising the level of financial disclosure and its impact on the quality and integrity of financial reports (Field study 2023-2024) Lawyer Hind Mansour Al-Balawi • The impact of the management by values (MBV) on the competitiveness of Saudi Arabia Hospitals Al-Qassim Region Dr. Gamaleldeen Osman Althair, Dr. Mohieldin Ali Mohieldin • The Impact of Forensic Accounting and Corporate Governance on Enhancing Accounting Transparency Lecturer Hanan Salih Jabur • The Knowledge Economy and Human Capital " A Literature Review" Ms. Halima Sharif Muhammad Al-Amrani, Prof. Reem Ali Al-Rabghi, Co-Prof. Rabab Abdulrahman Mujallid • The Role of 5S Workplace Organization in Promoting A Safe Work Environment in the Petroleum Sector “An Exploratory Study of the Opinions of Oil Sector Officials in Najaf Al-Ashraf” Dr. Yaser Hameed Mohammad Al-Hashimee, Prof. Mahdi Mohammadi Nasab • International Legal and Instiutional Mechanisms for Combating Corruption Lawyer Animar Ali Zaher